Gold-catalysed nitroalkyne cycloisomerization - synthetic utility - Dhote, Pawan S.; Halnor, Swapnil V.; Ramana, Chepuri V. (Chemical Record, 2021)
The gold-catalysed intramolecular redox cyclization of o-alkynylnitrobenzens documented by Professors Naoki Asao and Yoshinori Yamamoto is an important discovery that has opened two complementary research domains. Advancing this cyclization with other metals as well as developing new methods around the products that result from this reaction is one aspect that has seen growing interest. On the other hand, the idea of generating alpha-oxo gold carbenes via oxygen transfer to alkynes has established another important aspect in gold-catalysis. In this account, we will be dealing with the first aspect, which revolves around the internal redox cyclization of nitroalkynes (trivially called as nitroalkyne cycloisomerization), focusing mainly on the gold-complexes and the synthetic methods developed around it from our group and from other groups, and also providing the details of similar transformations documented with other metals so that the complementary reactivity/diversity of these transformations could be appreciated.
Keywords: alpha-Oxo Gold Carbene; Anthranil; Gold-catalysis; Internal Redox Cyclization; Isatogen